FACTORS INFLUENCING INDIVIDUAL SAVING BEHAVIOR: A LITERATURE REVIEW - EMENIDO, Shine (Journal of process management and new technologies, 2025)
Saving is crucial for financial stability and economic growth. However, many struggles to balance saving and spending due to low financial literacy and insufficient income. This study examined the factors that influence saving behavior of individuals in the Philippines to address barriers to effective saving habits. Specifically, this research aims to fill the gap in identifying the factors influencing saving behavior among Filipinos. Using a qualitative methodology, the study systematically reviewed and compared prior literature’s methodologies, objectives, and findings, to identify significant and common factors influencing saving habits. The results showed the factors influencing saving behavior are as follows: parental socialization, financial literacy, self-control, and peer influence; sociodemographic factors including education, income and gender, family background, attitude, financial literacy, and locality, financial attitude toward saving and self-efficacy. Furthermore, this research may help address issues that result in Filipinos not having enough income to set aside savings. In conclusion, this study emphasizes the importance of saving as it can impact a nation’s growth by contributing to capital accumulation, financial resilience, and economic stability, driving long-term growth, and reducing the vulnerability of the Philippine economy to external shocks.